(untitled) (Journal of Hama University, 2019)
Among various types of Motors, the hybrid stepper motor (HSM) is the most commonly used in precise motion control systems. It can be driven by digital ways with open loop control; this is the basic advantage of HSM over other type of motor. The simple control has demonstrated a poor dynamic performance. Since the stepper motor is used generally in high accuracy applications that require a high level of dynamic performance, the open loop control system might be low in both efficiency and accuracy. Thus, closed loop control system is the perfect replacement in the case at hand. We have provided, in this research, an adequate analytical study to the motor’s main characteristic; we have reached to the characteristics relating to position, torque, speed, and current by building a two phase HSM motor model in (MATLAB/SIMULINK) environment. We have controlled the current in two ways: proportional integrated controller (PI controller) and Hysteresis controller. A comparison has been achieved between motor’s response to speed, torque, and position in both of the control system has been under taken. The results we acquired have demonstrated that current control by PI controller has a high level of dynamic with less overshoot. Moreover, it is faster in stability.